A Descriptive Case Study of Using Line Application for Learning Writing - Paskalina Widiastuti Ratnaningsih (Universitas Sulawesi Barat, 2018)
Abstract Writing as part of English skills is highly concerned in the present days. The development of technology influences the use of media for teaching-learning activities. This paper aims at discovering students’ learning in English writing by using Line application as the media for learning. As one of the applications in the smartphone, Line application can be used in the teaching-learning activities. A task-based instruction is applied in the study. The method of study is case-study. The data were gathered with observation, interview, and document review. Holistic analysis was conducted after getting the data. The research result is writtten in descriptive. The description is divided into major themes. The themes are mainly in the scope of the use of technology for writing. Keywords: case study, line application, writing, task-based instruction